2018
DOI: 10.4103/jispcd.jispcd_222_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyaluronic acid added to suture material and its relationship with bacterial colonization: An in vitro study

Abstract: Aims and Objectives:The aims of this study were to evaluate the presence of Staphylococcus aureus and Escherichia coli, in polyglycolic acid (PGA) 4-0 and silk sutures, with or without hyaluronic acid (HA) treatment.Materials and Methods:This in vitro study measured S. aureus and E. coli growth on PGA and silk sutures, through incubation in agar media for 24 h. The suture length was 10 cm and divided into three parts: A (8 h), B (16 h), and C (24 h), which were observed every 8 h, followed by suspension on a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“… Small sample size (10 patients only). Syafilda et al 2019 16 To compare post-odontectomy wound healing time using silk and catgut sutures NRCT Third molar impaction surgery SS Catgut 7 days On day 1 and day 7 of the surgery, the catgut sutures have a mean score of wound healing time that is better than silk sutures. However, the time needed to perform suture of cat gut is longer.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Small sample size (10 patients only). Syafilda et al 2019 16 To compare post-odontectomy wound healing time using silk and catgut sutures NRCT Third molar impaction surgery SS Catgut 7 days On day 1 and day 7 of the surgery, the catgut sutures have a mean score of wound healing time that is better than silk sutures. However, the time needed to perform suture of cat gut is longer.…”
Section: Resultsmentioning
confidence: 99%
“…Nylon (polyamide) sutures had equal amounts of aerobes and anaerobes showing CFUs (≈300 sutures × 104/suture). Correspondingly, the effectiveness of hyaluronic acid (HA) at reducing bacterial accumulation in silk and PGA sutures (PGA) was examined in vitro by Sudhair et al, 16 and results showed that the mean S aureus and E coli CFUs were significantly higher on non-HA-treated silk than on HA-treated silk sutures. E coli CFUs were significantly higher on non-HA-treated PGA sutures than on HA-treated PGA sutures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations